ANALISIS PENGARUH DISIPLIN DAN LINGKUNGAN KERJA TERHADAP KINERJA DI HOTEL SANTIKA PREMIERE DYANDRA MEDAN - Wanda Ismanda Sirait; Khamo Waruwu; Hilman Lubis (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
The purpose of this study was to determine the influence of work discipline and work environment which are directly related to performance. Good work discipline and work environment can have an impact on increasing performance values. which with high discipline and a comfortable environment can provide changes in achieving goals to improve the performance of the Santika Premiere Dyandra Hotel Medan. This study was conducted at the Santika Premiere Dyandra Hotel Medan. The method used is quantitative descriptive research. The sampling technique uses the sloving formula with a set sample size of 67 respondents. As independent variables, namely work discipline and work environment, while the dependent variable is performance. The analytical tools used include validity tests, reliability tests, multiple linear regression analysis and hypothesis testing used is a partial test (t test). The results of hypothesis testing show that the first hypothesis (H1) work discipline and the second hypothesis (H2) are accepted. The results of testing the first hypothesis (H1) obtained results that have a positive and significant effect on performance. These results Testing the second hypothesis (H2) obtained results that the work environment has a positive and significant effect on performance. Discipline and work environment have a simultaneous influence on performance, contributing 77.60%, while the remainder is influenced by unknown variables.